Technological Innovation in Central and Eastern Europe: What’s the Contribution of Innovation Policy? - Loukil, Kamilia (The Economics and Finance Letters, 2017)
If European Union member states are technologically lagging behind other member countries, especially Eastern European countries, it is important to analyze whether or not public policies contribute to the reduction of this gap. In this respect, our study examines the effect of public innovation policy on technological innovation in Central and Eastern European countries. The estimation of panel data model for 10 countries over the 1998-2013 period show that innovation policy in these countries is not efficient.